Interaction between SNCA, LRRK2 and GAK increases susceptibility to Parkinson's disease in a Chinese population - Wen-Juan Yu; Lan Cheng; Nan-Nan Li; Ling Wang; Eng-King Tan; Rong Peng (eNeurologicalSci, 2015)
PD is a complex disease, and may result from gene–gene and gene–environment interactions. There are limited studies on gene–gene interactions in PD. We and others have previously shown that SNCA rs356219, LRRK2 (rs2046932 and rs7304279) and GAK (rs1564282) are risk factors in sporadic PD. Since the expression of SNCA and neurotoxicity of alpha-synuclein are affected by LRRK2 and GAK, we hypothesize that their genetic risk variants may interact with each other. Here we investigated the interaction of SNCA rs356219, LRRK2rs7304279 and rs2046932 and GAK rs1564282 using the Multifactor Dimensionality Reduction (MDR) in a Chinese PD patient–control series (534 patients and 435 controls) and the cumulative risk effect of SNCA, LRRK2 and GAK. The MDR analysis showed a significant gene–gene interaction between the rs356219 of SNCA, rs2046932 of LRRK2 and rs1564282 of GAK. Moreover, individuals with increasing numbers of variants had an increasing likelihood of having PD, compared with those carrying none of the variants. The estimated OR for developing PD in individuals carrying 3 variants was 5.89. We demonstrated for the first time that SNPs in SNCA, LRRK2 and GAK interacted with each other to confer an increased risk of PD. In addition, PD risk increased cumulatively with the increasing number of variants.